2012
DOI: 10.1088/0022-3727/45/42/425103
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced UV emission from ZnO nanoflowers synthesized by the hydrothermal process

Abstract: ZnO nanoflowers were synthesized by the hydrothermal process at an optimized growth temperature of 200 • C and a growth/reaction time of 3 h. As-prepared ZnO nanoflowers were characterized by x-ray diffraction, scanning electron microscopy, UV-visible and Raman spectroscopy. X-ray diffraction and Raman studies reveal that the as-synthesized flower-like ZnO nanostructures are highly crystalline with a hexagonal wurtzite phase preferentially oriented along the (1 0 1 1) plane. The average length (234-347 nm) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 39 publications
(50 reference statements)
8
34
0
Order By: Relevance
“…Figures 1B-1E shows the HR-SEM images of zinc oxide nanoparticles that have formed nanoflower and nanorod like structures. Similar structures were observed using hydrothermal methods at elevated temperatures (2008C) over 3 h [5]. Till date there have been no reports of zinc oxide nanoflowers synthesized using algae.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Figures 1B-1E shows the HR-SEM images of zinc oxide nanoparticles that have formed nanoflower and nanorod like structures. Similar structures were observed using hydrothermal methods at elevated temperatures (2008C) over 3 h [5]. Till date there have been no reports of zinc oxide nanoflowers synthesized using algae.…”
Section: Resultssupporting
confidence: 73%
“…Bulk zinc oxide absorbs around 373 nm due to its wide band gap whereas a red shift of 13 nm was observed in our sample. This has been previously observed in ZnO nanoflowers and was ascribed to the oriented attachment of the nanorods [5,17]. ZnO nanoparticles were also synthesized at a pH of 7 and the spectrum was found to be blue-shifted compared to the bulk; at more alkaline conditions no nanoparticles were formed (data not shown).…”
Section: Resultssupporting
confidence: 72%
“…The initial reactants were dissolved in distilled water and maintained at a pH of about 8–10. The reactants were placed in a sealed Teflon‐lined stainless steel autoclave and maintained at a temperature of 200 °C for 3 h under autogenous pressure . After the heating process, the autoclave was allowed to cool naturally to reach room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…A sharp band edge emission in near UV region at 390 nm and a wide broad band extending laterally between 450 nm and up to 700 nm with peaks centered around 580 nm were clearly observed in the emission spectra. 31 The edge emission for ZnO nanodumbbells shows significant presence of defects. It is extensively reported that broad DLE band is a defect-related emission.…”
Section: Mechanism For Nanodumbbells Formationmentioning
confidence: 99%